2016
DOI: 10.1371/journal.pone.0154719
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Biochemical Pools of Golgi Phosphoprotein 3 in the Human Breast Cancer Cell Lines MCF7 and MDA-MB-231

Abstract: Golgi phosphoprotein 3 (GOLPH3) has been implicated in the development of carcinomas in many human tissues, and is currently considered a bona fide oncoprotein. Importantly, several tumor types show overexpression of GOLPH3, which is associated with tumor progress and poor prognosis. However, the underlying molecular mechanisms that connect GOLPH3 function with tumorigenicity are poorly understood. Experimental evidence shows that depletion of GOLPH3 abolishes transformation and proliferation of tumor cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…Kenneth L. Scott raised the hypothesis that GOLPH3 interacted with VPS35 and the tetramer to recycle receptor for key molecules, thus regulating downstream mTOR signaling (19). Tenorio et al found that the cytosolic and membrane components of the three breast cell lines had biochemical differences in GOLPH3, that was that, in cancer cells, part of the overexpressed GOLPH3 was modified by differentiation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Kenneth L. Scott raised the hypothesis that GOLPH3 interacted with VPS35 and the tetramer to recycle receptor for key molecules, thus regulating downstream mTOR signaling (19). Tenorio et al found that the cytosolic and membrane components of the three breast cell lines had biochemical differences in GOLPH3, that was that, in cancer cells, part of the overexpressed GOLPH3 was modified by differentiation (34).…”
Section: Discussionmentioning
confidence: 99%
“…After the final wash, coverslips were mounted onto glass slides with Fluoromount‐G (SouthernBiotech, Birmingham, AL, USA). Images of fixed cells were acquired with an AxioObserver.D1 microscope equipped with a PlanApo ×63 oil‐immersion objective (NA 1.4) and an AxioCam MRm digital camera (Carl Zeiss GmbH, Jena, Germany), using similar settings described previously (34), or with an Olympus FluoView FV1000 scanning unit fitted on an inverted Olympus IX81 microscope equipped with a PlanApo ×60 oil‐immersion objective (NA 1.4; Olympus, Tokyo, Japan), using similar settings as described previously (35). Alternatively, images of fixed cells were acquired by a DeltaVision OMX system (GE Healthcare Life Sciences, Issaquah, WA, USA) for superresolution by structured illumination microscopy (SIM), using similar settings as described previously (36, 37).…”
Section: Methodsmentioning
confidence: 99%
“…The corrected fluorescent signal in each cell of each image was used to determine the total integrated pixel intensity per cell area by ImageJ 1.44o software [Image Processing and Analysis in Java; National Institutes of Health (NIH), Bethesda, MD, USA; http://imagej.nih.gov/]. Colocalization analyses and estimation of the Pearson's correlation coefficient (38) were performed as described in Wong and Holzbauer (35).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate how the overexpression of GOLPH3 might influence its roles in the oncogenesis of breast cancer, the group of Mardones compared some of the biochemical and cellular characteristics of GOLPH3 in the two human breast cancer cell lines MCF7 and MDA-MB-231 with those of GOLPH3 in the non-tumorigenic human breast cell line MCF 10A [81]. They showed that the three breast cell lines possess biochemical distinct pools of GOLPH3 and that the GOLPH3 protein distributes differently in cytosolic and membrane-bound pools in the different breast cell lines.…”
Section: Expression Of Golph3 Is Correlated With Breast Cancer Prolifmentioning
confidence: 99%